Evaluation of a tele-refraction model to address the lack of human resources in Kenya - Shadrack Muma; Jyoti Naidoo; Khathutshelo Percy Mashige; Tshubelela Sello Simon Magakwe (PLoS ONE, 2026)
Background Uncorrected Refractive Errors (URE) constitute a significant public health concern in Kenya, where limited availability of qualified eye care professionals continues to impede equitable access to refractive services. This shortage is particularly acute in rural and underserved regions, resulting in significant unmet visual health needs. The implementation of telemedicine; specifically, a tele-refraction model utilizing low-cost, portable devices, has emerged as a viable and cost-effective approach to decentralize service delivery, enhance accessibility, and mitigate the burden of URE at the primary healthcare level. Methods This non-inferiority diagnostic accuracy study was conducted in Machakos. County, Kenya, to evaluate the performance of the OneSight EssilorLuxottica Foundation’s ClickCheck™ tele-refraction model in comparison with conventional face-to-face retinoscopy, which served as the reference (gold) standard. A total of 92 patients (184 eyes) were examined. The tele-refraction procedure entailed a trained technician performing objective refraction using the ClickCheck™ device, followed by subjective refinement under the real-time supervision of a remote optometrist via telecommunication. Statistical analyses assessed the agreement between the final subjective prescriptions obtained from both methods, focusing on the clinical conformity rate for spherical equivalent (SE), cylindrical power, and power vector components within a strict clinical tolerance limit of ±0.50 diopters (D). Results The study demonstrated a high level of clinical concordance between the telerefraction model and the conventional gold-standard refraction method. The mean difference in spherical equivalent (SE) for objective refraction was minimal (+0.08 D), indicating negligible bias between the two techniques. Importantly, the final subjective prescriptions exhibited excellent clinical interchangeability, with 93.01% of cases falling within the ± 0.50D tolerance for SE and 94.41% within the same tolerance for cylindrical power magnitude. Furthermore, for clinically significant astigmatism, axis alignment showed complete conformity within the 10 degrees tolerance range across all cases. Conclusion The tele-refraction model using the ClickCheck™ device, combined with remotely guided subjective refraction, demonstrated accuracy, reliability, and non-inferiority when compared with conventional in-person refraction. These findings substantiate the clinical validity of tele-refraction, which holds the potential to mitigate the acute shortage of eye care professionals and to enhance equitable access to refractive error correction services among underserved populations in Kenya.